GoEkopz: An E-Koperasi and Marketplace Synergy of Koperasi MSMEs Model Platform - Case Study: Koperasi Giat, eKopz Startup, PPKM Community - Hendriyanto, Robbi; Agung, Anak Agung Gde; Mandasari, Rizza Indah Mega; Widaningsih, Sri; Setyorini, Retno (Society of Visual Informatics, 2023)
With a population of 273.5 million in 2020, the people's economy is very important for Indonesia. The populist economic model has existed in Indonesia for a long time, locally known as â€œKoperasiâ€. However,Â KoperasiÂ could not keep up with information and technology in the industrial 4.0 era. When other industrial models adopt information technology massively,Â KoperasiÂ seems to struggle to shift from the conventional model. Slowly but surely, Koperasi become less popular, especially among Generation Z, who considers information technology part of their daily needs and lifestyle. The scope ofÂ Koperasiâ€™sbusiness shrinks and becomes limited, along with their business capital. On the other hand, information technology provides opportunities for small and medium-sized entrepreneurs. The data shows that this sector contributes to 60.5% of the national GDP, absorbs 96.9% of the workforce, and provides 99.9% of total employment. Unfortunately, many Micro, Small, and Medium Enterprises (MSME) have limited capital and tend to prefer fintech services that offer easier accessibility thanÂ Koperasi. This paper aims to propose an E-KoperasiÂ and the synergy ofÂ KoperasiÂ and MSMEs model platform, specifically the digital marketplace platform. We design the platform requirements using the Software Requirement Specification with the User Acceptance Test. As a result, an application is developed as a model platform available for Koperasi and MSMEs. The platform is proposed to support the Governmentâ€™s program to digitalize the Koperasi and the MSMEs and increase their competitiveness in Industrial 4.0.